First case of human bacteraemia by Catabacter hongkongensis in Scandinavia. (January 2017) - Kaden, R.; Thelander, M.; Engstrand, L.; Herrmann, B.
Abstract: Catabacter hongkongensis was isolated and cultured from human blood for the first time in Scandinavia. The patient, an 83-year-old man from Dalarna, Sweden, recovered without antibiotic treatment, although a high mortality rate associated with C. hongkongensis infection had been reported from China, Canada and France. The genome of the strain ABBA15k was sequenced, assembled and analysed. In contrast to the type strain of the species HKU16 T, no antibiotic resistance was observed in Scandinavian strain ABBA15k. The strain was deposited as CCUG 68271, and the draft genome sequence is available from the DNA Data Bank of Japan (DDBJ), the European Molecular Biology Laboratory (EMBL), and GenBank under the accession number LLYX00000000.